Toxoplasma gondii Infection Is Associated with Mitochondrial Dysfunction in-Vitro - Syn, Genevieve; Anderson, Denise; Blackwell, Jenefer M.; Jamieson, Sarra E. (Frontiers in Cellular and Infection Microbiology, 2017)
Upon invasion of host cells, the ubiquitous pathogen Toxoplasma gondii manipulates several host processes, including re-organisation of host organelles, to create a replicative niche. Host mitochondrial association to T. gondii parasitophorous vacuoles is rapid and has roles in modulating host immune responses. Here gene expression profiling of T. gondii infected cells reveals enrichment of genes involved in oxidative phosphorylation (OXPHOS) and mitochondrial dysfunction 6 hours post-infection. We identified eleven hub genes (HIF-1α, CASP8, FN1, POU5F1, CD44, ISG15, HNRNPA1, MDM2, RPL35, VHL and NUPR1) and ten predicted upstream regulators, including 4 endogenous regulators RICTOR, KDM5A, RB1 and D-glucose. We characterised a number of mitochondrial parameters in T. gondii infected human foreskin fibroblast cells over a 36 hour time-course. In addition to the usual rapid recruitment and apparent enlargement of mitochondria around the parasitophorous vacuole we observed fragmented host mitochondria in infected cells, not linked to cellular apoptosis, from 24 hours post-infection. An increase in mitochondrial superoxide levels in T. gondii infected cells was observed that required active parasite invasion and peaked at 30 hours post-infection. Measurement of OXPHOS proteins showed decreased expression of Complex IV in infected cells at 24 hours post-infection, followed by decreased expression of Complexes I and II at 36 hours post-infection. No change occurred in Complex V. No difference in host mitochondrial membrane potential between infected and mock-infected cells was observed at any time. Our results show perturbation of host mitochondrial function following T. gondii infection that likely impacts on pathogenesis of disease.